Tantric Nuances Arguing Gender Order in Mithila Paintings - Paneru, Pragya (Molung Educational Frontier, 2020)
This article reviews the Tantric influence in the traditional Mithila paintings and argues how Tantra’s emphasis on femininity can challenge the traditional patriarchal notion toward women in general. In doing so, firstly, the article examines the studies in Tantra and its views toward women in general. Secondly, it analyzes the studies in Mithila paintings and their connection with Tantra and the actual women context in the Maithil community. Lastly, it reviews some of the examples of Mithila paintings to study the presence of tantric symbols, as claimed by the studies in Mithila paintings, followed by a conclusion. The findings suggest that being a highly patriarchal culture, with limited authority to women even in their personal life decisions, Mithila culture yet contains seeds of resistance within itself. On the one hand, Maithil women lack the liberty of sexual expressions, decision makings, and involvement in outdoor activities as the veil in their head symbolically separates them from the rest of the society, except the traditional feminine chores. On the other hand, traditional Mithila paintings mocks the patriarchy through the feminine images and symbols as eminent cosmic power, a source of creation, and destruction. The Tantric images and signs in Mithila paintings shout out the power of femininity, challenging patriarchal beliefs of men as a center and women as a margin. This article stresses that Tantric dualism and its equal emphasis on femininity reflected in Mithila paintings can be used as a powerful religious, cultural, and artistic tool to empower women and subvert the general binary of men and women. Mithila paintings that have become a source of economic empowerment, emotional expressions, and means of awareness of women in the present-day, can also be used to harmonize the male-female tensions and as an effective religious, cultural, and artistic device to tear-off shackles of patriarchy.